2021
DOI: 10.1021/acsami.1c16767
|View full text |Cite
|
Sign up to set email alerts
|

All-Climate High-Voltage Commercial Lithium-Ion Batteries Based on Propylene Carbonate Electrolytes

Abstract: Propylene carbonate (PC)-based electrolytes have many attractive advantages over the commercially used ethylene carbonate (EC)-based electrolytes like a wider operating temperature and higher oxidation stability. Therefore, PC-based electrolytes become the potential candidate for lithium-ion batteries with higher energy density, longer lifespan, and better low-and high-temperature performance. In spite of the superiority, PC is incompatible with the graphite anode because PC fails to passivate the graphite ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…28,29 In addition, previous reports have indicated that the combination of cyclic and linear carbonate might provide higher performance for K-DCBs. 30 Consequently, combining EC, PC, and DEC is conducive to preparing high concentration electrolytes for K-DCBs.…”
Section: Sustainablementioning
confidence: 99%
“…28,29 In addition, previous reports have indicated that the combination of cyclic and linear carbonate might provide higher performance for K-DCBs. 30 Consequently, combining EC, PC, and DEC is conducive to preparing high concentration electrolytes for K-DCBs.…”
Section: Sustainablementioning
confidence: 99%
“…[4] In the cryogenic range below −10 °C, most LIBs retain only a modest fraction that protects graphite from solvent co-intercalation and electrolyte decomposition. [18][19][20] However, due to the sacrificial nature of these additives, only limited cycles (<150) at low temperatures were attained.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many attempts to design EC‐free electrolytes rely on the use of film‐forming additives such as fluoroethylene carbonate (FEC) or vinylene carbonate (VC), so‐called “enablers”, to produce SEI that protects graphite from solvent co‐intercalation and electrolyte decomposition. [ 18–20 ] However, due to the sacrificial nature of these additives, only limited cycles (<150) at low temperatures were attained.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate electrolytes have drawn tremendous attention in recent years in view of their superior anodic stability and nonflammability features, making them highly desirable for high-voltage batteries. Unfortunately, phosphate solvents are known to be highly corrosive toward reactive sodium metal anodes, thus largely impeding their utilization for sodium metal-based batteries. , In the past decade, intensive work has been devoted to optimizing the composition of phosphate electrolytes with the aim of building a more friendly anode/electrolyte interface. , Nevertheless, highly efficient sodium deposition with a high round-trip Coulombic efficiency is yet to be realized. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…25,30−32 Nevertheless, highly efficient sodium deposition with a high round-trip Coulombic efficiency is yet to be realized. 26,27,31,33,34 In this manuscript, we rationally design and propose for the first time a high-performance ternary phosphate electrolyte composed of a cost-effective sodium bis(trifluoromethane sulfonyl) imide (NaTFSI) salt, nonflammable triethyl phosphate (TEP) as a dominating solvent, and fluoroethylene carbonate (FEC) as a functional co-solvent for Na 3 V 2 (PO 4 ) 2 F 3 −cathode-based HV-SMBs. It is unveiled that the FEC addition into the phosphate electrolyte introduces an additional coordination with sodium ions without largely altering the original TEP−Na + intercalation, resulting in a preferential reduction on sodium metal anodes and the formation of a fluoride-rich interphase.…”
Section: Introductionmentioning
confidence: 99%